Cardiac dose is associated with immunosuppression and poor survival in locally advanced non-small cell lung cancer. Issue 3 (September 2018) - Contreras, Jessika A.; Lin, Alexander J.; Weiner, Ashley; Speirs, Christina; Samson, Pamela; Mullen, Daniel; Campian, Jian; Bradley, Jeffrey; Roach, Michael; Robinson, Clifford
Abstract: Purpose: Studies have associated increased radiation therapy (RT) heart dose with cardiac toxicity. Others have correlated RT-related immunosuppression with worsened survival. Given the large vascular volumes irradiated during locally advanced non-small cell lung cancer (LA-NSCLC) treatment, we hypothesized an association between increased heart dose and immunosuppression. Methods: We identified 400 LA-NSCLC patients treated with definitive RT ± chemotherapy between 2001 and 2016. Absolute lymphocyte counts (ALC), absolute neutrophil counts (ANC), and neutrophil-to-lymphocyte ratio (NLR = ANC/ALC) were analyzed pre-RT, during RT, and post-RT. Multivariable analysis (MVA) was performed to correlate Clinical factors with both hematologic toxicity and overall survival. An upper tertile threshold to increase specificity of NLR was chosen to dichotomize continuous hematologic variables. Results: Median follow up was 17 months (range 0.2–174 months) in all patients and 46 months (range 0.2–161 months) in survivors. A total of 94% of patients had stage III disease and 77% received concurrent chemo radiation. Two-year overall survival (OS), freedom from local recurrence (FFLR), and freedom from distant metastases (FFDM) was 42%, 60% and 45%, respectively. Median survival was 18 months. On MVA for OS ( n = 207), male gender (Hazard Ratio [HR] 1.7; 95% CI 1.2–2.3), RT alone (HR 2.1; 95% CI 1.9–4.0), the percentage of heart receiving ≥50 Gy (V50) (HR 1.02; 95% CI 1.01–1.03), and higher NLR at 4 months (HR 1.02, 95% CI 1.01–1.03) were associated with reduced OS. ALC nadir was not associated with treatment outcomes. NLR >10.5 was associated with decreased OS ( p < 0.001) and decreased FFDM ( p = 0.04). On MVA evaluating factors associated with hematological toxicity ( n = 247), adjuvant chemotherapy (HR 2.6; 95% CI 1.3–5.0; p = 0.006), RT alone (HR 3.6; 95% CI 1.1–12; p = 0.04), and heart V50 >25% (HR 2.0; 95% CI 1.1–3.5; p = 0.02) were associated with a NLR >10.5 4 months post-RT. Conclusion: RT related immunosuppression is associated with worse patient outcomes, and may represent a source of increased mortality beyond cardiac toxicity alone.